The Perceived Value of Digital Transformation in Businesses: The Experience of Six Executives in Cameroon (Global Journal of Management and Business Research, 2025)
The aim of this research is to identify the density of perceived benefits and sacrifices of the digitization process implemented within companies, based on semi-directive interviews centered on the experience discourse of managers. It is therefore part of an analytical logic of perceived value concerning the digital transformation of companies from the point of view of their managers. The results obtained reveal some thirty positively perceived values of digital transformation, as well as the changes induced by it in the cases studied within Cameroonian companies.
Keywords: Perceived value; digital transformation; experience; managers